2014
DOI: 10.1557/opl.2014.566
|View full text |Cite
|
Sign up to set email alerts
|

High quality and high speed cutting of 4H-SiC JFET wafers including PCM structures by using Thermal Laser Separation

Abstract: The silicon carbide (SiC) market is gaining momentum hence productivity in device manufacturing has to be improved. The current transition from 100 mm SiC-wafers to 150 mm SiC-wafers requires novel processes in the front-end as well as the back-end of SiC-chip production. Dicing of fully processed SiC-wafers is becoming a bottleneck process since current state-of-the-art mechanical blade dicing faces heavy tool wear and achieves low throughput due to low feed rates in the range of only a few mm/s. This paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Electrical characteristics: TLS diced JFET devices were assembled using direct copper bonding substrates and were afterwards electrical characterized by measuring the on state and the blocking characteristic. It could be shown that the TLS process does not influence the electrical characteristics of these SiC devices [4]. Fig.…”
Section: Discussion Of Results Achieved With Tlsmentioning
confidence: 92%
“…Electrical characteristics: TLS diced JFET devices were assembled using direct copper bonding substrates and were afterwards electrical characterized by measuring the on state and the blocking characteristic. It could be shown that the TLS process does not influence the electrical characteristics of these SiC devices [4]. Fig.…”
Section: Discussion Of Results Achieved With Tlsmentioning
confidence: 92%
“…The TLS technology is a two-step process [3]. A first short pulsed laser scribe initiates a crack along the dicing street and cuts through the metal of the PCM structures.…”
Section: Thermal Laser Separation (Tls)mentioning
confidence: 99%
“…The back side metallization of the SiC chip is also separated without damages, delamination (Fig. 8) [3] and negative effects on the sawing foil. TEM analysis shows no damage at the chip side walls [4].…”
Section: Thermal Laser Separation (Tls)mentioning
confidence: 99%
“…Thermal Laser Separation (TLS) defines the starting point through the initial scratch, using tensile stress generated by the heating area and cooling area to break the material apart. 6 However, irregular propagation of microcracks can affect chips performance. Stealth Dicing (SD) 7 focuses a laser beam inside the material to form modified layers and separates the chip by splitting or film expansion, which solves the problem of the method mentioned above.…”
mentioning
confidence: 99%